Growth behaviour and yield of fine rice genotypes in boro season - Mannan, MA; Bhuiya, MSU; Hossain, SMA; Mamun, MA (Bangladesh Journal of Agricultural Research, 2008)
Bangladesh J. Agril. Res. 32(4) : 663-669